Can we manage marine mammal bycatch effectively in low‐data environments?. Issue 3 (3rd January 2021) - Punt, André E.; Siple, Margaret C.; Francis, Tessa B.; Hammond, Philip S.; Heinemann, Dennis; Long, Kristy J.; Moore, Jeff; Sepúlveda, Maritza; Reeves, Randall R.; Sigurðsson, Guðjón Már; Víkingsson, Gísli; Wade, Paul R.; et al.
Abstract: Determining acceptable rates of human‐caused mortality in low‐data situations is a concern for many taxa world‐wide. An established approach for determining acceptable levels of human‐caused mortality of marine mammals and other species of conservation concern is the Potential Biological Removal (PBR) framework, but PBR requires near‐unbiased estimates of absolute abundance, constraining its use in systems with limited data. We develop three alternative methods for identifying acceptable levels of human‐caused mortality for long‐lived, slowly reproducing species, using indices of relative abundance combined with estimates of bycatch mortality in fisheries, and evaluate these methods using simulations similar to those used to develop PBR. Across a variety of scenarios, the parameters of the three methods can be tuned to achieve conservation performance similar to that of PBR in scenarios that represent nearly ideal conditions. However, these methods produce lower and more variable bycatch mortality limits, depend upon reasonably accurate estimates of bycatch mortality and are more sensitive to uncertainties. Synthesis and applications . Here we develop three alternative methods that expand the toolbox of approaches available for use in determining marine mammal conservation reference points for human‐caused mortality when it is not possible to apply the more standard, data‐hungry PBR approach. These approaches may be useful in supporting the establishment of new bycatch management programmes, or until estimates of absolute abundance become available. Abstract : Here we develop three alternative methods that expand the toolbox of approaches available for use in determining marine mammal conservation reference points for human‐caused mortality when it is not possible to apply the more standard, data‐hungry Potential Biological Removal approach. These approaches may be useful in supporting the establishment of new bycatch management programmes, or until estimates of absolute abundance become available. Resumen: Determinar tasas aceptables de mortalidad antropogénica en situaciones de pocos datos, es una preocupación para muchas especies en todo el mundo. Un enfoque ampliamente utilizado para estimar niveles aceptables de mortalidad antropogénica sobre mamíferos marinos y otras especies de interés para la conservación es la Remoción Biológica Potencial (PBR en inglés), el que, sin embargo, requiere estimaciones de abundancia absoluta con bajo sesgo, lo que restringe su uso en situaciones con datos limitados. Desarrollamos tres métodos alternativos para identificar niveles aceptables de mortalidad antropogénica para especies longevas y de baja tasa reproductiva, utilizando índices de abundancia relativa combinados con estimaciones de mortalidad por captura incidental en pesquerías, y evaluamos estos métodos utilizando simulaciones similares a las empleadas para desarrollar el PBR. Para una diversidad de escenarios, los parámetros de los tres métodos pueden ser ajustados para lograr un desempeño de conservación similar al del PBR en escenarios que representan condiciones casi ideales. Sin embargo, estos métodos producen límites de mortalidad por captura incidental más bajos y más variables, dependiendo de estimaciones razonablemente precisas de mortalidad por captura incidental, y que son más sensibles a incertidumbres. Síntesis y aplicaciones . desarrollamos tres métodos alternativos que amplían las herramientas de enfoques disponibles para su uso en la determinación de puntos de referencia de conservación de mamíferos marinos por mortalidad antropogénica cuando no es posible aplicar la aproximación del PBR, que es más estándar pero que necesita de más datos. Estos enfoques pueden ser útiles para apoyar el establecimiento de nuevos programas de manejo de la captura incidental, o hasta que se disponga de estimaciones de abundancia absoluta.